Integrating three prongs of social control: China's pandemic response - Lin, Kai (Policing during the COVID-19 pandemic, 2024)
Often coined as the “zero-COVID policy,” China’s unique approach to pandemic management entails strategies such as aggressive mass testing, strict quarantine protocols for visitors and those exposed to the virus, and invasively thorough contact tracing. The implementation of these strategies relies on the concerted deployment of several structural processes and mechanisms available to the Chinese government, including a massive network of public surveillance, deterrent criminal justice policies and practices regarding pandemic rules violations, ubiquitous and profoundly embedded semiformal social control at the neighborhood level, and effective information campaigns and propaganda against COVID-19. This chapter describes China’s pandemic control strategies (up until March 2023), measures, and the key actors involved and compares it with pandemic rules enforcement in other countries such as the UK and Australia. It contextualizes such a response against the three prongs of social control and the broader tendency of intensified surveillance and law enforcement deterrence in China, particularly during the past decade.